Analysis of Cholera Epidemics in Sarawak From 1994-2003 and Molecular Characterization of Vibrio Cholerae Isolated from the Outbreaks in Malaysia - Benjamen, Patrick Guda (2006)
In this study, the epidemiologic and demographic data on cholera cases obtained from Sarawak for the ten years period from 1994 to 2003 and the factors associated with the emergence and spread of cholera and its control were reported. In addition, this study also evaluates and differentiates the molecular characteristics of toxigenic Vibrio cholerae isolated during the recent cholera outbreaks in Sarawak and Peninsula Malaysia. A total of 32 strains were examined for their antibiotics sensitivity, RAPD-PCR fingerprinting and the presence of ctx gene. Thirteen of the strains were V. cholerae 01 isolated from Miri division, seven from 1999 outbreak in Samarahan Division, 10 from 2001 outbreak in Selangor and two V. cholerae 0139 from 2002 outbreak in Penang. In the ten years period (1994-2003), 1672 cholera patients were recorded in Sarawak. High incidence of cholera was observed during and just after the unusually strong El Niño years of 1997 to 1998 when a very severe and prolonged drought occurred in Sarawak. Large outbreaks occurred in northern part of Sarawak (Bintulu, Miri, and Limbang) rather than the central (Kapit, Sarikei, Sibu) and southern region (Kuching, Samarahan, Sri Aman). The Orang Ulu, Iban and the Malays were the three most infected ethnic groups in Sarawak. Data analysis showed a high incidence of cholera among low-income laborers and rural house wives as opposed to the well-paid workers from government and private sectors. Infants and non-school children made up 15% of the cases. This suggested that household transmission occurs widely. The majority of the patients were the active adult group from 19 to 59 years. This finding was typical of many food-borne outbreaks where adults gathered to attend festive parties or funeral feasts. Various intervention activities and preventive measures such as surveillance, quarantine, treatment, monitoring and improving community sanitation, and health education of poor communities were performed by the Health Department and the local authorities during and after the major 1997 - 1999 epidemics. These measures effectively prevented the emergence and spread of further epidemics. All the isolates, except V. cholerae 0139, were highly sensitive to most of the twenty-one antibiotics tested. All the isolates (100%) were sensitive to ampicillin, piperacin, cephalothin, cefuroxime, cefotaxime, ceftazidime, tetracycline, nadilic acid, ciprofloxacin, gentamicin and netilmicin; 94% of the isolates were sensitive to amoxicillin/clavulanic acid, ampicillin/sulbactam, trimethoprim, trimethoprim/sulfamethoxazole combination, chloramphenicol, and rifampin; 38% sensitive to streptomycin and sulfamethoxazole. However, all the strains were resistant to metronidazole and teicoplanin. All the 32 V. cholerae strains also expressed the ctx genes, which almost exclusively present in the 01 and 0139 serotypes only. The ctx genes distinguish these epidemic serotypes from the non-01 serotypes. Randomly amplified polymorphic DNA (RAPD) analysis was used to analyze the genetic relatedness of all the 32 V. cholerae strains. Two primers that is GEN 1-50-03 and GEN 1-50-08 generated polymorphism in all 32 strains, producing type able and reproducible results. From the dendrogram generated, using RAPDistance software (Version 1.04),. two main groups were observed which were subdivided into two clusters each. The Selangor’s isolates and the 0139 strains formed one group whereas the Sarawak’s isolates made up the other group, thus defining their different sources of origin. The Sarawak’s isolates generated five types of profile (S1-S5) in which three of the profiles (S1, S4, S5) were specific to Miri outbreak while the other two profiles (S2 and S3) were common to both Miri and Samarahan outbreaks delineating their clonal relatedness.